Strategies of the control of an outbreak of Leptospiral infection in dairy cattle in northeastern Brazil - Pimenta, C. L. R. M.; Costa, D. F.; Silva, M. L. C. R.; A. Júnior, J. P.; Malossi, C. D.; Ullmann, L. S.; Nogueira, D. B.; Santos, C. S. A. B.; Higino, S. S. S.; Alves, C. J.; Azevedo, S. S. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2019)
Leptospirosis is a zoonotic disease of global importance, caused by pathogenic bacteria belonging to the genus Leptospira. The infection has a wide geographical distribution, with higher occurrence in tropical regions, and each serovar is usually associated with a maintenance host.